2017
DOI: 10.1007/s00405-017-4832-0
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of cochlear implantation among children with genetic syndromes

Abstract: Cochlear implant recipients with genetic syndromes achieved similar levels auditory perception and speech intelligibility as their peers with a genetic syndrome. The presence of any of the genetic syndromes described herein should not be a contraindication to cochlear implant provision, as it would have a positive impact on the patients' sensory perception and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
0
16
0
10
Order By: Relevance
“…Studies of cochlear implantation in children with Pendred syndrome found that they have better speech perception compared to children who are deaf due to enlarged vestibular aqueduct not caused by Pendred syndrome despite the possibility of mild surgical complications due to the inner ear malformations caused by Pendred (Kontorinis et al, 2011;van Nierop et al, 2016;Mikkelsen et al, 2019;Mey et al, 2020). Other studies indicate that early diagnosis of SNHL, followed by cochlear implantation and rehabilitation, is also beneficial in Usher and Waardenburg Syndromes (Young et al, 1995;Loundon et al, 2003;Cullen et al, 2006;Hartel et al, 2017;Alzhrani et al, 2018;Nair et al, 2020).…”
Section: Current Use Of CI In Congenital Hearing Lossmentioning
confidence: 99%
“…Studies of cochlear implantation in children with Pendred syndrome found that they have better speech perception compared to children who are deaf due to enlarged vestibular aqueduct not caused by Pendred syndrome despite the possibility of mild surgical complications due to the inner ear malformations caused by Pendred (Kontorinis et al, 2011;van Nierop et al, 2016;Mikkelsen et al, 2019;Mey et al, 2020). Other studies indicate that early diagnosis of SNHL, followed by cochlear implantation and rehabilitation, is also beneficial in Usher and Waardenburg Syndromes (Young et al, 1995;Loundon et al, 2003;Cullen et al, 2006;Hartel et al, 2017;Alzhrani et al, 2018;Nair et al, 2020).…”
Section: Current Use Of CI In Congenital Hearing Lossmentioning
confidence: 99%
“…Dwoje dzieci cierpiało na izolowany zespół Dandy' ego-Walkera, a u dwojga pozostałych współwystępowały choroby genetyczne. U wszystkich opisanych dzieci zdiagnozowano obustronną czuciowo-nerwową głuchotę [8,16,17,18] (tabela 1).…”
Section: Wynikiunclassified
“…Niepowodzenie rozwoju mowy wystąpiło prawdopodobnie z powodu nieregularnych kontroli u specjalistów i niewystarczającej rehabilitacji słuchowej. Pacjentka źle wypadła w testach oceniających jej mowę i wyniki słuchowe (tabela 2) [18].…”
Section: Wyniki Słuchowe Osób Z Zespołem Dandy'ego-walkera I Implantem śLimakowymunclassified
See 1 more Smart Citation
“…Кохлеарна имплантация по повод на загуба на слуха е извършена в рамките на проучване от типа "случай-контрола" при 13 деца с различни генетични синдроми (синдром на Варденбург, синдром на Ушер или синдром на Денди-Уолкър) или албинизъм и при други 12 деца без генетични синдроми (2). Окончателната чисто тонална аудиометрия показва нормална находка до леко изразена загуба на слуха -от 23 dB при децата без генетични синдроми и от 26 dB -при децата с такива синдроми.…”
Section: намаление и загуба на слуха при генетични синдромиunclassified